Zollinger - Ellison Synckome - Liard, Washington; Geninazzi, Héctor; Bertullo, Hugo; Pizzarrosa, Carlos; Aguirre de García, Beatriz; Roble, Ana M; Otegui, Ismael; Perdomo, Roberto; Touya, Eduardo (Cirugía del Uruguay, 1978)
The latesf knowledge on the pathology diagnosis ánd treatment of the Zollinger - Ellison syndrome are considered. This is the first time in our experience that the pancreatic tumour and -its hepatic metastasis has been clinicaUy observed in Uruguay. It was diagno·sed from biopsies and by means of a radioimmunology, test of the circulating gastrine and that contained in tumour tissues.